Preparation of Solid Dispersions of Simvastatin and Soluplus Using a Single-Step Organic Solvent-Free Supercritical Fluid Process for the Drug Solubility and Dissolution Rate Enhancement - Uttom Nandi; Adejumoke Lara Ajiboye; Preksha Patel; Dennis Douroumis; Vivek Trivedi (MDPI AG, 2021)
The study was designed to investigate the feasibility of supercritical carbon dioxide (scCO2) processing for the preparation of simvastatin (SIM) solid dispersions (SDs) in Soluplus® (SOL) at temperatures below polymer's glass transition. The SIM content in the SDs experimental design was kept at 10, 20 and 30% to study the effect of the drug-polymer ratio on the successful preparation of SDs. The SIM-SOL formulations, physical mixtures (PMs) and SDs were evaluated using X-ray diffraction (XRD), differential scanning calorimetry (DSC), attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR), scanning electron microscopy (SEM), and dissolution studies. The scCO2 processing conditions and drug-polymer ratio were found to influence the physicochemical properties of the drug in formulated SDs. SIM is a highly crystalline drug; however, physicochemical characterisation carried out by SEM, DSC, and XRD demonstrated the presence of SIM in amorphous nature within the SDs. The SIM-SOL SDs showed enhanced drug dissolution rates, with 100% being released within 45 min. Moreover, the drug dissolution from SDs was faster and higher in comparison to PMs. In conclusion, this study shows that SIM-SOL dispersions can be successfully prepared using a solvent-free supercritical fluid process to enhance dissolution rate of the drug.